Brazil’s first free-mating laboratory colony of Nyssorhynchus darlingi - Maisa da Silva Araujo; Alice Oliveira Andrade; Najara Akira Costa dos Santos; Dhélio Batista Pereira; Glaucilene da Silva Costa; Paula Frassinetti Medeiros de Paulo; Carlos Tong Rios; Marta Moreno; Luiz Hidelbrando Pereira-da-Silva; Jansen Fernandes de Medeiros (Revista da Sociedade Brasileira de Medicina Tropical)
Abstract INTRODUCTION: The lack of highly-productive Nyssorhynchus darlingi laboratory colonies limits some studies. We report the first well-established laboratory colony of Ny. darlingi in Brazil. METHODS: Mosquitoes were collected from Porto Velho and were reared at the Laboratory of Fiocruz/RO. After induced mating by light stimulation in the F1 to F6, the subsequent generations were free mating. Larvae were reared in distilled water and fed daily until pupation. RESULTS: In 11 generations, the colony produced a high number of pupae after the F5 generation. CONCLUSIONS: These results demonstrate the potential for permanently establishing Ny. darlingi colonies for research purposes in Brazil.